Benjamin Shambaugh and the intellectual foundations of public history - Conard, Rebecca (Book collections on Project MUSE., 2002)
Conard draws upon an unpublished, mid-1940's biography by research historian Jacob Swisher to trace the forces that shaped Shambaugh's early years, his administration of the State Historical Society of Iowa, his development of applied history and commonwealth history in the 1910's and 1920's, and the transformations in his thinking and career during the 1930's. Framing this intriguingly interwoven narrative are chapters that contextualize Shambaugh's professional development within the development of the historical profession as a whole in the late nineteenth and early twentieth centuries and.